PENGARUH METODE SURVEY, QUESTION, READ, RECITE AND REVIEW (SQ3R) TERHADAP HASIL BELAJAR SISWA - Adiyaksa Fahmi Marat; Kasman Rukun (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The problem in this study is that there are still many TKJ class X students at Padangsidimpuan Vocational High School 3 who receive a learning value below the minimum criteria standard in Computer Systems subjects. This study discusses the effect of the Survey, Question, Read, Recite and Review (SQ3R) method on the learning outcomes of TKJ students in class X on Computer Systems lessons at SMK 3 Padangsidimpuan. This research was conducted with the aim to determine the differences in learning outcomes of class X students in Computer Systems subjects after learning using the SQ3R method in learning. The research was an experimental study, with sampling using Purposive Sampling techniques so that the experimental group was class X TKJ 1 by applying the SQ3R method and the control group was class X TKJ 2 using the Problem Based Learning (PBL) method. Where testing of instruments is done in class XI TKJ who have studied Computer System subjects. Based on the results of the study, the average price obtained by the experimental class is 78.94 while the average price obtained by the control class is 75.97. The results of hypothesis calculations with a significant degree of 0.05 obtained by tcount (2.285)> t table (1,669). Then it was concluded that zero (H0) was rejected, while the alternative guess (Ha) was accepted. Judging from the percentage calculation of the learning outcomes of the experimental class and the control class, there is an effect of using the SQ3R method with a percentage of 3.91%, which means the value of student learning with the application of the SQ3R method is better in this study.Keywords: Survey Method, Question, Read, Recite and Review (SQ3R), learning outcomes